2012
DOI: 10.1007/10_2012_155
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Intravenously Injected Mesenchymal Stem Cells and Significance for Clinical Application

Abstract: Mesenchymal stromal cells (MSCs) have initially been characterized as a fibroblastlike cell population that can be expanded readily in vitro, and is able to support hematopoiesis in vitro and in vivo. By serendipity it was discovered that MSCs can also be administered into the bloodstream. This mode of application formed a major breakthrough in the clinical use of MSCs, because MSC transplantation was found to cure severe immune hyperactivation states such as graft-versus-host disease after allogeneic bone mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 81 publications
1
33
0
Order By: Relevance
“…Although not yet a fully validated therapy for SCI, the safety of this approach has already been established through preclinical SCI studies , its clinical application to other conditions affecting the CNS, including multiple sclerosis and bone marrow transplantations. Nevertheless, this approach is not without its limitations, osteoblastic differentiation of infused MSCs has been reported within lung tumors and although this has not been observed in injury and degeneration models, this possibility should not be dismissed. Furthermore investigation is necessary prior to clinical translation.…”
Section: Discussionmentioning
confidence: 99%
“…Although not yet a fully validated therapy for SCI, the safety of this approach has already been established through preclinical SCI studies , its clinical application to other conditions affecting the CNS, including multiple sclerosis and bone marrow transplantations. Nevertheless, this approach is not without its limitations, osteoblastic differentiation of infused MSCs has been reported within lung tumors and although this has not been observed in injury and degeneration models, this possibility should not be dismissed. Furthermore investigation is necessary prior to clinical translation.…”
Section: Discussionmentioning
confidence: 99%
“…Multipotent mesenchymal stromal cells (MSCs) harbor great potential for regenerative and immunomodulatory therapies and are currently under investigation in numerous clinical trials, the majority thereof relying on systemic infusion. A major drawback in MSC therapy appears to be the incomplete understanding of fate and function of MSCs following systemic administration . Recent attention has been attributed to the fact that many MSC therapeutics are cryobanked for immediate “off‐the‐shelf” availability in the clinic .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of high importance to elucidate how MAPC modulate the features of myeloid cell types since intravenously transplanted cells are likely to be localized in close proximity with myeloid cells in the CNS and periphery [37, 61, 69]. Overall, we showed that inflammatory macrophages are able to regulate the immunomodulatory properties of rMAPC in vitro, thereby warranting confirmatory in vivo studies.…”
Section: Discussionmentioning
confidence: 66%